The doctrine of scripture : an introduction - Thompson, Mark, 1959 March 12- (Wheaton, Illinois : Crossway, 2022)
"Centered on the words of Scripture and especially the teaching of Jesus himself, this volume unpacks the doctrine of Scripture as taught by the church through the ages, helping to strengthen readers' confidence in God's word"--
Includes bibliographical references and indexes.
Keywords: Bible -- Evidences, authority, etc. -- History of doctrines